Sistem Aplikasi Rental Kamera Studio SM Fotografi Berbasis Java Menggunakan Metode Prototype - M. Ikhsan; Zulhipni Reno Saputra Elsi; Dedi Haryanto (STMIK Budi Darma, 2023)
This research aims to build a camera rental system that facilitates transactions between managers and renters without having to go to the SM Fotografi studio first using the prototype method. The method used by researchers to create this SM Fotografi camera rental application is the prototype method. Producing a system can make it easier for users to get information to rent cameras online without having to come to the studio. The system is made as simple as possible, so that users can easily recognize each function of the tools in this application. The system can be used to rent 1 or more cameras within each camera brand. Use of the system in the form of a self-made application with real-time data presentation in the form of letters, numbers and tables